Suspended Matter Distribution in Beypore Estuary - M.N., Muraleedharan Nair; P.T., Lakshmanan (Fishery Technology, 2025)
Suspended matter concentration (SMC) in the Beypore Estuary during pre-monsoon and monsoon periods from ten stations during 1987-1988 are presented. Variations in suspended matter load at different water levels over the tidal cycles were monitored at one station. Relatively higher values were obtained during monsoon months compared to premonsoon period. The highest value of 143 mg.l"1 was observed during September 1987 while the lowest value of 2 mg.l"1 was obtained during January 1988. Inverse relationship between suspended matter concentrations and salinity was observed during monsoon months. However, the relationship did not hold good during post-monsoon and summer months. Observations during tidal cycles have shown that bottom waters always registered higher values in suspended matter load, most probably due to the re-suspension of bottom mud owing to scouring effect of tidal currents. Sediment content was found to co-vary with the increase in salinity during summer months. Material brought in through river run off contributes mainly to the suspended matter load in monsoon period while particles of marine origin have the major share during summer season.